Symbols of the costume in the oriental theater Mahabharata - Ahmed, Aseel Laith (Al-Adab Journal, 2021)
The art of theatre is that art that mixes between music and dance, from one side, and between color, lighting, costumes and design, from another side. It is also seen from a third side that shows the artistic plastic creation of the artist in making the costumes of actors. These costumes help the actor to play the role through what is called the outfit. The outfit is described as a disjunctive material between the actor and the character he- she plays. It is manufactured from many kinds of fabrics such as, cloth, cotton and wool, and wool, and then colored to create the gestures and symbols to express either joy, sadness or horror of the character on the stage. The eastern theatre, then, depended on costumes and masks for they add so many expressions in addition to music, dancing and gestures. Therefore, this study "the symbolic indications of the costume in eastern theatre " – (Mahabharata as an exemplar) comes up with four chapters; chapter one includes the problem, need and significance of the study as well as identifying the most important terms of the study.Chapter two includes the theoretic frame in two separate sections;1- the historical characteristics of the costume in eastern theatre.2- the data of the symbol on the costume in eastern theatre.Chapter two ends up with the outcomes of the theoretic frame.Chapter three shows the procedures of the study. A purpsed sample is given here to match the study.Chapter four includes the most significance results and their interpretations. The study is ended by a list of sources.